2011
DOI: 10.1158/0008-5472.can-11-1144
|View full text |Cite
|
Sign up to set email alerts
|

miR-221 Silencing Blocks Hepatocellular Carcinoma and Promotes Survival

Abstract: Patients with advanced hepatocellular carcinoma (HCC) face a dismal prognosis due to a lack of any effective therapies. To address this situation, we conducted a preclinical investigation of the therapeutic efficacy of oligonucleotides directed against the oncogenic microRNA miR-221 which has been implicated in HCC. Of 9 chemistries evaluated, we determined that a 2′-O-methyl phosphorothioate-modified anti-miR-221 oligonucleotide was most effective at reducing proliferation in vitro. A cholesterol-modified iso… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
160
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(165 citation statements)
references
References 46 publications
5
160
0
Order By: Relevance
“…In one notable study, systemic delivery of a cholesterol-tagged antimiR-221 to orthotopic HCC tumors was found to reduce tumor cell proliferation and promote survival. 164 In a second study, anti-miR-221 oligonucleotides were found to exhibit significant antitumor activity in the TG221 transgenic mouse model, where a significant reduction in the number and size of tumors in the treated mice was confirmed with histopathological analyses. Significant downregulation of miR-221 levels has also been detected in liver tissues of anti-miR-221-treated mice, thereby confirming the ability of these molecules to inhibit endogenous miR-221 145 ( Table 2).…”
Section: Mirna-based Therapiesmentioning
confidence: 94%
“…In one notable study, systemic delivery of a cholesterol-tagged antimiR-221 to orthotopic HCC tumors was found to reduce tumor cell proliferation and promote survival. 164 In a second study, anti-miR-221 oligonucleotides were found to exhibit significant antitumor activity in the TG221 transgenic mouse model, where a significant reduction in the number and size of tumors in the treated mice was confirmed with histopathological analyses. Significant downregulation of miR-221 levels has also been detected in liver tissues of anti-miR-221-treated mice, thereby confirming the ability of these molecules to inhibit endogenous miR-221 145 ( Table 2).…”
Section: Mirna-based Therapiesmentioning
confidence: 94%
“…miR-221 also seems to be a good molecular target. In fact, it has been reported that the 2 -Omethylphosphorothioate-modified oligonucleotide anti-miR-221 reduces cell proliferation and increases the markers of apoptosis and cell cycle arrest, increases the doubling time of the tumor and growth thereby increasing the survival in mice (Park et al, 2011). So also Callegari et al (2012) showed that in transgenic mice in which cirrhosis and cancer are induced by diethylnitrosamine, the overexpression of miR-221 determines an inhibition of its target: CDKI1b/p27 and CDKI1c/p57.…”
Section: Mir-221mentioning
confidence: 99%
“…In addition to the LNA technology, cholesterol-modified miRNAs (cholanti-miRs) exhibit improved pharmacokinetics and anti-tumor efficacy. For example, chol-antimiR-221 suppresses effectively liver tumor growth in vivo [140].…”
Section: Mirna Therapeutics In Cancer Metabolismmentioning
confidence: 99%